Patterns of Sequence and Expression Diversification Associate Members of the PADRE Gene Family With Response to Fungal Pathogens - Didelon, Marie; Khafif, Mehdi; Godiard, Laurence; Barbacci, Adelin; Raffaele, Sylvain (Frontiers in Genetics, 2020)
Pathogen infection triggers extensive reprogramming of the plant transcriptome, including numerous genes the function of which is unknown. Due to their wide taxonomic distribution, genes encoding proteins with Domains of Unknown Function (DUFs) activated upon pathogen challenge likely play important roles in disease. In Arabidopsis thaliana, we identified thirteen genes harboring a DUF4228 domain in the top 10% most induced genes after infection by the fungal pathogen Sclerotinia sclerotiorum. Based on functional information collected through homology and contextual searches, we propose to refer to this domain as the pathogen and abiotic stress response, cadmium tolerance, disordered region-containing (PADRE) domain. Genome-wide and phylogenetic analyses indicated that PADRE is specific to plants and diversified into 10 subfamilies early in the evolution of Angiosperms. PADRE typically occurs in small single-domain proteins with a bipartite architecture. PADRE N-terminus harbors conserved sequence motifs, while its C-terminus includes an intrinsically disordered region with multiple phosphorylation sites. A pangenomic survey of PADRE genes expression upon S. sclerotiorum inoculation in Arabidopsis, castor bean, and tomato indicated consistent expression across species within phylogenetic groups. Multi-stress expression profiling and co-expression network analyses associated AtPADRE genes with the induction of anthocyanin biosynthesis and responses to chitin and to hypoxia. Our analyses reveal patterns of sequence and expression diversification consistent with the evolution of a role in disease resistance for an uncharacterized family of plant genes. These findings highlight PADRE genes as prime candidates for the functional dissection of mechanisms underlying plant disease resistance to fungi.